2009
DOI: 10.1177/1074840709331639
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Letters in Nursing

Abstract: This article summarizes the first research to be completed on the Family Systems Nursing intervention of therapeutic letters. In the Family Nursing Unit (FNU) at the University of Calgary, therapeutic letters have been used for more than 22 years in work with families experiencing illness and suffering. Using Gadamerian philosophical hermeneutic inquiry, the research explores 11 therapeutic letters sent and received in the work with three families (four participants) seen in the FNU. Textual interpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Receiving a personally written letter communicating closeness and warmth written by health professionals is likely an uncommon experience but seemed to be a valuable part of the FamHC. The healing potential of closing letters has previously been documented in other research (Bell et al, 2009;Moules, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Receiving a personally written letter communicating closeness and warmth written by health professionals is likely an uncommon experience but seemed to be a valuable part of the FamHC. The healing potential of closing letters has previously been documented in other research (Bell et al, 2009;Moules, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…All assignments were based on reflective discussions or reflective writing on the health-promoting conversations and the theoretical ground behind the practice. The students found this a bit repetitive and suggested that the final theoretical assignment instead included writing a closing letter, also called a therapeutic letter [9,43] to their fictive families. On the other hand, students commented that the reflections supported their knowledge and performance of health-promoting family conversations.…”
Section: Discussionmentioning
confidence: 99%
“…Family nursing scholars in Canada (University of Calgary, University of Montreal), Iceland (University of Iceland), and Sweden (Linnaeus University, Umea University) have led the development of this knowledge through dedicated research units and programs of research that focused on both family nursing research about therapeutic conversations between nurses and families and teaching students and practicing nurses how to conduct therapeutic conversations with families (Bell, 2008;Benzein, Hagberg, & Saveman, 2008;Benzein, Olin, & Persson, 2015;Duhamel, 2010;Östlund, Bäckström, Saveman, Lindh, & Sundin, 2016;Sigurdardottir, Garwick, & Svavarsdottir, 2016;Svavarsdottir et al, 2015;Svavarsdottir, Sigurdardottir, & Tryggvadottir, 2014;Wright & Bell, 2009). Families consistently report that family nursing therapeutic conversations are helpful to them and remarkably different than the "usual conversations" that occur with health care professionals (Bell & Wright, 2015;Gisladottir & Svavarsdottir, 2016;Houger Limacher, & Wright, 2006;McLeod & Wright, 2008;Moules, 2009;Östlund & Persson, 2014;Robinson & Wright, 1995;Sigurdardottir et al, 2016;Tapp, 1997;Thirsk & Moules, 2013;West, Bell, Woodgate, & Moules, 2015). Wright (2015) has offered fascinating explanations from brain science about why family nursing conversations are often experienced by families as healing.…”
Section: What Do We Know About Family Nursing Therapeutic Conversations?mentioning
confidence: 99%